2019
DOI: 10.1111/jfpe.13042
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasonic‐assisted enzymatic extraction of β‐carotene from orange processing waste

Abstract: In this research, extraction of β‐carotene pigment from orange processing waste was investigated by combining ultrasonic and enzymatic processes using ethanol solvent. In order to optimize the extraction conditions, the effect of pectinase enzyme concentration [0–5% (w/w)], ultrasonic time (10–120 min), and pH of solution (3.5–6) on dependent variables of β‐carotene content, antioxidant activity, color parameters of L*, a*, and b*, and browning index (BI) of extracts was investigated using response surface met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…UAE has been used to extract carotenoids from different fruits and vegetables by-products such as acerola, guava, genipap and umbu seeds and peels ( 72 ), carrot pomace ( 73 , 81 ), cantaloupe peel ( 82 ), mandarin peel ( 54 , 83 , 84 ), Gac fruit peel ( 63 ), mango peel and paste ( 85 ), peel of different varieties of orange ( 38 , 43 , 48 ), orange pomace ( 86 ), pepper leaves ( 87 ), pomegranate peel ( 55 ), pumpkin peel ( 88 , 89 ), purple passion fruit peel ( 90 ), sea buckthorn pomace ( 49 , 91 , 92 ), tomato peel and seeds ( 31 , 93 95 ), and arthropods by-product such as shrimp shell and cephalothorax ( 40 , 96 98 ). According to these studies, carotenoids can be used as a natural pigment directly in the preparation of various food products such as butter, salad dressing, beverages, ice cream, desserts, candy, bakery, edible oils, meet products, cosmetics, pharmaceutical products, also as an ingredient in feed for aquatic animals and pets.…”
Section: Extraction Of Natural Pigments With Ultrasound-assisted Extr...mentioning
confidence: 99%
See 1 more Smart Citation
“…UAE has been used to extract carotenoids from different fruits and vegetables by-products such as acerola, guava, genipap and umbu seeds and peels ( 72 ), carrot pomace ( 73 , 81 ), cantaloupe peel ( 82 ), mandarin peel ( 54 , 83 , 84 ), Gac fruit peel ( 63 ), mango peel and paste ( 85 ), peel of different varieties of orange ( 38 , 43 , 48 ), orange pomace ( 86 ), pepper leaves ( 87 ), pomegranate peel ( 55 ), pumpkin peel ( 88 , 89 ), purple passion fruit peel ( 90 ), sea buckthorn pomace ( 49 , 91 , 92 ), tomato peel and seeds ( 31 , 93 95 ), and arthropods by-product such as shrimp shell and cephalothorax ( 40 , 96 98 ). According to these studies, carotenoids can be used as a natural pigment directly in the preparation of various food products such as butter, salad dressing, beverages, ice cream, desserts, candy, bakery, edible oils, meet products, cosmetics, pharmaceutical products, also as an ingredient in feed for aquatic animals and pets.…”
Section: Extraction Of Natural Pigments With Ultrasound-assisted Extr...mentioning
confidence: 99%
“…Szabo et al ( 95 ) confirmed that the mixture of hexane/acetone lead to obtaining the maximum extraction of carotenoids recovered from tomato by-products. In addition, saponification processes were used to separate the carotenoids from ether bounds, methanolic solution of KOH (20%) was used in these cases ( 84 ), also enzymatic pre-treatment with cellulase and pectinase or polygalacturonase has been shown useful to accelerate extraction processes ( 81 , 86 ).…”
Section: Extraction Of Natural Pigments With Ultrasound-assisted Extr...mentioning
confidence: 99%
“…Citrus peel waste has been studied for several of its bioactive components, such as the pectin, dietary fiber, and essential oils like limonene [62]. Additionally, β-carotene has been extracted from orange processing waste by ultrasonic and enzymatic processes with pectinase and ethanol solvent, showing potential for commercial production [67]. The conversion of agricultural residues and biomass to value-added rare sugars and prebiotic oligosaccharides has been studied (Table 3), as they are a potential ingredient for functional foods with benefits to human health [114].…”
Section: Value Added Biomoleculesmentioning
confidence: 99%
“…In all these organisms, these compounds display various shades of black, blue, brown, green, orange, pink, red or yellow colours (Simpson et␣al ., 2012). Synthetic colourants and their residual toxic chemicals are harmful to plants, animals and even human beings, and lead to cancer and mutation in adults and allergic dermatitis, hyperactivity problems in children (Shahram & Dinani 2019). Therefore, considering the above mentioned negative aspects of synthetic colourants, for human health and safety, environment friendliness, the addition of natural colourants in foods, cosmetics and pharmaceutical products is preferred as an alternative to synthetic colours (Maran et␣al ., 2013).…”
Section: Introductionmentioning
confidence: 99%